State of the Art on Kidney Development: How Nephron Endowment at Birth Can Shape Our Susceptibility to Renal Dysfunction Later in Life - Fanos, Vassilios; Gerosa, Clara; Loddo, Cristina; Faa, Gavino (American Journal of Perinatology, 2019)
In the present article, we discuss the following topics: (1) the fetal programming of adult kidney diseases and (2) the role of neonatologists in the regenerative renal medicine, based on the activation of resident renal SC. Here, we report the most important steps of our collaboration between neonatologists, nephrologists, and pathologists. Nephrologists should be more interested in clinical data regarding the first month of life in the womb of their adult patients, being particularly focused on birth weight and on the weeks of gestation at birth, without forgetting data regarding maternal status during gestation and neonatal asphyxia. Neonatologists should be aware that any preterm or low birthweight infant should be considered as a subject with fewer glomeruli, probably predicted to develop renal disease later in life.
Keywords: nephrogenesis; kidney development; chronic kidney disease; fetal programming of kidney diseases; renal regenerative medicine